Data Analytic on Energy Consumption in UTHM Building Campus - Mohd Nizam, Nur Adila; Lim, Alvin John (Recent Trends in Civil Engineering and Built Environment, 2024)
This research looks into the energy use of several buildings at Tun Hussein Onn University (UTHM). The main objective is to assess the energy consumption of Faculty Civil Engineering and Built Environment (FKAAB), Faculty of Technology Management and Business Faculty of Technology Management and Business (FPTP), Faculty of Electrical and Electronic Engineering (FKEE), Faculty of Computer Science and Information Technology (FSKTM), Faculty  of Technical and Vocational Education (FPTV), and Perpustakaan Tunku Tun Aminah. This impacts UTHM buildings. It's also about figuring out why high of energy usage. This will be done by analyzing the energy utilization of the UTHM buildings. Energy management is measuring and reducing energy consumption in a building. The next step in analysing energy use at UTHM buildings is to collect data over the last three years. It will collect data from, 2018-2020. To analyse the data, it must first calculate the building's size and space. Besides that, the building's level must be considered. After obtaining all necessary data, data analytics will be used to analyze the data. Data analytics is the study of analysing factual data to conclude using Power BI (Business Intelligent) software from Microsoft. This programme will provide dynamic visualisations, capabilities through an easy-to-use interface.From the analysis UTHM buildings FKAAB, FPTP, FKEE, FSKTM, FPTV, and Library. Consume more energy due to weather, conditions, building construction, and materials utilised. It may be deduce that the appliances and human behavior cause the UTHM building's excessive energy usage. Next, it may use data analytics to categorize the energy usage of each building and equipment on the building in Universiti Tun Hussein Onn (UTHM) Campus and compare the energy usage of each building.